Cisplatin palbociclib combination differentially modulates PTEN AKT signaling via Hsp90 in hepatocellular carcinoma cells - Hameis M. Sleem; Aya A. Ali; Eman Ramadan (Scientific Reports)
Abstract Hepatocellular carcinoma (HCC) presents a significant global health challenge, marked by high mortality and recurrence. This study investigated the synergistic potential of cisplatin and palbociclib (C + P) against HCC cell lines. RT-qPCR revealed that C + P significantly downregulated HCC-related genes, including Hsp90, β-catenin, and components of the PI3K/AKT/mTOR pathway, compared to cisplatin alone and controls. Western blotting confirmed a reduction in phosphorylated AKT (P-AKT) with palbociclib and C + P, while PTEN, a tumor suppressor, was upregulated in the C + P group. Annexin V-FITC assays demonstrated a substantial increase in apoptosis in palbociclib and C + P treated cells. Cell cycle analysis indicated S and G0–G1 phase arrest with C + P, suggesting a combined cytotoxic effect. Scratch wound assays showed that both palbociclib and C + P significantly inhibited cell migration compared to cisplatin and controls. These findings suggest a promising synergistic effect of C + P in overcoming cisplatin resistance in HCC. However, further research is needed to fully elucidate the complex interactions between these drugs.